If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6k + 24 = 3k + -12 Reorder the terms: 24 + 6k = 3k + -12 Reorder the terms: 24 + 6k = -12 + 3k Solving 24 + 6k = -12 + 3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3k' to each side of the equation. 24 + 6k + -3k = -12 + 3k + -3k Combine like terms: 6k + -3k = 3k 24 + 3k = -12 + 3k + -3k Combine like terms: 3k + -3k = 0 24 + 3k = -12 + 0 24 + 3k = -12 Add '-24' to each side of the equation. 24 + -24 + 3k = -12 + -24 Combine like terms: 24 + -24 = 0 0 + 3k = -12 + -24 3k = -12 + -24 Combine like terms: -12 + -24 = -36 3k = -36 Divide each side by '3'. k = -12 Simplifying k = -12
| 12v^7w^9+16v^4w^5x^8=0 | | 11+5(k+1)=3k-(6k-6) | | F(x)=lhx+2 | | 4.2x-2.1=1.68-5.4x | | -26+3x=-36+6x | | 5-3x=7x+5 | | 102=5w+17 | | -9(x-4)=-3x+42 | | 12-2x=2x+8 | | X=8-3(-3) | | A=10x+y+2 | | 21+3x=56 | | -9x-4y=-4 | | -x=-3+2x | | 210p=1890 | | 3x-5=12+3x | | 6n+10=-4n+50 | | 8*n=32 | | 16x^2-27e=0 | | 10=6x+3 | | 9x+11=6x+-9+3 | | 3x-18=12+7x | | 4x-4x+5=12 | | 4+5(x-2)=6+7(x-2) | | (10-2x)(8-2x)(x)=f(x) | | -8+x=4x+1 | | cos+2sec=-3 | | -16=2(1-5x)+4 | | x+3.5=8.5-9x | | 10x-5(x-2)=30 | | 7-4x-3x-5=6x+1+2x-3 | | =(4x-3)(2x+7)-(4x-3)(6-x) |